Kebijaksanaan Perburuhan di Perkebunan Sumatera Timur pada Masa Kolonial - Sjafri Sairi (Antropologi Indonesia, 1997)
Why the labors of Javanese origin who worked in tobacco plantations in North Sumatera, in the colonial period, were not able to quit from their work and left the plantation, eventhough the payments they received were unworthy? The author argues that three factors are responsible to this situation. First is the punale sanctie, or the labor act. It was said in the act that the colonial government was eligible to punish a labor as he refused to work, or left the plantation. In the gamble the labors would usually be lost and run out of money. The last factor is the introduction of opium, which eventually makes the labors addicted, they ruin their life.